Response to chicco et al. communication entitled 'Management and outcomes of mammalian bite injuries during COVID-19 and implications for future practice' Published: November 07, 2020DOI:https://doi.org/10.1016/j.bjps.2020.10.090. Issue 5 (May 2021) - Friebel, T.R.; Gardiner, S.; Southall, C.; Akhavani, M.
Summary: The Covid-19 pandemic has forced us to treat mammalian bite injuries more conservatively as resources were redirected to the Covid effort resulting in limited availability of hospital beds and theatre space. When comparing our outcomes before and during the first Covid-19 lockdown, this more conservative approach, which resulted in 24% less admissions and 19% less washouts in theatre, did not result in an increased infection rate. An increased rate of bite injuries during the national lockdown period was also noted. We support the conclusion by Chicco et al. that the majority of patients with bite injuries can 'safely be managed with washout under local anaesthesia, oral antibiotics and discharge on the same day with safety net advice'. It is interesting that in some aspects of our care we may find Covid-19 has been beneficial in de-medicalising management of certain injuries and conditions.